Fieldwork Assignments in the Anthropology of Religion: A Practical Guide - Buckser, Andrew (Religion and society, 2010)
This article discusses structural, logistical, and administrative issues associated with the use of participant observation assignments in teaching the anthropology of religion. Fieldwork presents extraordinary opportunities for teaching students about the nature of cultural difference, but it also poses pedagogical challenges that require careful planning and supervision. The article reviews problems including the scope and nature of the observation, student preparation and guidance, connecting with fieldsites, presentation formats, issues of ethics and confidentiality, and university administrative considerations.